Conciliation & care experiences in pandemic times of researchers at the University of Granada - Valenzuela-Vela, Lorena; Reyes Ruiz de Peralta, Natalia; Gallardo-Nieto, Elena (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
This article is based on the research project “Impacts of the COVID-19 pandemic and confinement on female researchers in the Social Sciences area of the University of Granada from a gender perspective” (2021/GR/UIG/000001). This study used a qualitative method, with an in-depth and semi-structured interviews to focus on the results obtained on the emotional impact, showing the different repercussions according to the different situations; the conciliation, concluding that the transformations of the spaces and of the time that telework supposed, have been negative; and care tasks, in which feminist practices have been incorporated to alleviate inequalities.